Power, politics, and the origin of the Chinese Exclusion Era - Campbell, Jessica, author; Gudmestad, Robert, advisor; Payne, Sarah, committee member; Souza, Caridad, committee member (Colorado State University. Libraries, 2017)
This study places the origins of the Chinese Exclusion Era (1823-1882) in a larger regional, national, and international context to reveal that the Chinese Exclusion Era was not a direct cause and effect relationship between labor and policy, but rather a negotiation between various groups including immigrants, laborers, politicians, and businessmen, where each group worked in its own self-interest to achieve or eliminate the exclusion of Chinese immigrants in the United States. This study focuses on issues of race, class, and gender, with particular emphasis on the ways in which existing structures and institutions within the United States such as the black-white binary, democracy, and capitalism shaped the reception and ultimate exclusion of immigrants.